Study of Positive Corona Plasma on Organdy Silk: Analysis of Current–Voltage Characteristics and Their Influence on Water Absorption Time in Moving Samples (International Journal of Scientific Research in Science and Technology, 2025)
A study was conducted to investigate the effects of positive corona discharge plasma radiation on organdy silk fabric samples in motion. The primary objectives were to characterize the current–voltage (I–V) relationship of the positive corona plasma for both stationary and moving samples, and to evaluate the water absorption behavior of irradiated samples under dynamic conditions. The plasma was generated using a DC high-voltage power supply connected to electrodes arranged in a multi-point-to-plane configuration, integrated with a conveyor system. In this setup, the multi-point electrode functioned as the anode, while the plane electrode served as the cathode. Plasma irradiation was applied to the fabric samples by varying three key parameters: irradiation duration (t), electrode gap, and sample movement speed. To assess the impact of plasma treatment, a water absorption test was performed by applying 1 mL of water to the irradiated surface and recording the time required for complete absorption. The characterization results revealed that the discharge current increased as the electrode gap decreased. Additionally, samples exposed to longer irradiation durations exhibited faster water absorption. Notably, samples irradiated at a speed of 13.13 cm/s absorbed water more quickly than those treated at 4.8 cm/s, indicating enhanced surface modification at higher movement speeds.This document provides some minimal guidelines (and requirements) for writing a research paper. Issues related to the contents, originality, contributions, organization, bibliographic information, and writing style are briefly covered. Evaluation criteria and due dates for the research paper are also provided.